The design and analysis of pipe diffusers for centrifugal compressors - Bennett, Ian (Cranfield University, 1997)
Diffusers are necessary to convert the high velocity head of centrifugal compressor discharge flow into useful static pressure. One diffuser type that has shown a great deal of promise, particularly at high pressure ratios, are pipe diffusers. These have been successfully incorporated into centrifugal compressor stages in North America since the early 1970’s. With their commercial sensitivity, however, little design or detailed flow information has been published, and most of this literature is old, dating back twenty years to the design’s conception. This thesis is a compilation of pipe diffuser information, formed from the limited literature works and an intensive experimental parametric study. Two themes run through this thesis and are brought about by different reader needs. The first need is for design information. This must show the strengths and weakness of pipe diffusers and be of sufficient accuracy to potentially produce designs at the first attempt. The second need is to understand the flows within the diffuser itself, in order that through this knowledge further improvements can be made. Both of these requirements are addressed in this thesis. The studies are centred on, what was originally, a Rolls-Royce research centrifugal compressor impeller of 6:1 pressure ratio operating at 35,000 rpm with a tip speed of 533ms'1 consuming up to a nominal 1MW of power. Significant modifications to the original compressor assembly were made to allow modular changes of diffuser and permit detailed measurement access. Initially, a vaneless diffuser investigation was carried out with the primary aim of determining the flow entering the diffusers. This was followed by a diffuser throat sizing exercise as it is well recognised that the diffuser throat has a governing control over the complete stage performance. An exercise in changing the number of diffuser pipes was then undertaken, followed by a hybrid diffuser investigation incorporating an oval, rather than circular, cross-section. In all of these cases, detailed flow measurements were carried out using both conventional pneumatic instrumentation and a purposely developed unsteady pressure measurement data acquisition system. This system enabled detailed traverses of the diffuser throats to be undertaken. These unique measurements shed new light on the flow ‘seen’ by the pipe diffuser channel. Computational investigations using computational fluid dynamics (CFD) codes are carried out to compliment the experimental investigations.